2012
DOI: 10.3382/ps.2012-02471
|View full text |Cite
|
Sign up to set email alerts
|

Associations of chicken Mx1 polymorphism with antiviral responses in avian influenza virus infected embryos and broilers

Abstract: Avian influenza virus (AIV) is a major respiratory disease of poultry that causes catastrophic losses to the poultry industry. The Mx protein has been shown to confer antiviral responses to influenza viruses in mice. One nonsynonymous substitution (S631N) in the chicken Mx protein is reported to be associated with resistance to AIV infection in vitro. The previous studies suggested controversy over whether this substitution in the Mx protein plays an important antiviral role in AIV infection in the chicken. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The recombinant H5N1 virus with the single MxA resistance mutation L283P (H5N1-NP-L283P) grew slightly less well than the parental H5N1 strain, while the double mutant virus H5N1-NP-R100I,F313Y showed comparable growth (Figure 5E). Intriguingly, the latter virus showed severely impaired replication efficiency in avian LMH cells which lack antiviral Mx proteins [37][39] (Figure S8). We conclude that MxA resistance is linked to impaired viral growth and may be easily lost in the absence of selective pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The recombinant H5N1 virus with the single MxA resistance mutation L283P (H5N1-NP-L283P) grew slightly less well than the parental H5N1 strain, while the double mutant virus H5N1-NP-R100I,F313Y showed comparable growth (Figure 5E). Intriguingly, the latter virus showed severely impaired replication efficiency in avian LMH cells which lack antiviral Mx proteins [37][39] (Figure S8). We conclude that MxA resistance is linked to impaired viral growth and may be easily lost in the absence of selective pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms of the Mx gene have been reported in multiple breeds of chickens, including Australorp, Fayoumi, Japanese native chickens, Indonesian native chickens, White Leghorns, Broilers and inbred laboratory lines [5], [7][10]. Most of these reports have focused primarily on exon 14 (13 th coding exon) and the S631N variant, though other non-synonymous variants have been identified in other exons, and multiple haplotypes have been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo work by Ewald et al [11] using commercial meat-type (broiler) chicks suggested that those with the N631 variant were more resistant to viral challenge than those with the S631 variant. However, other laboratories using primary chicken embryo fibroblast, transfected cells, chicken embryos, or chicks found no difference in the resistance to influenza virus infection regardless of which 631 variant was expressed [10], [12]–[15]. Furthermore, Schusser et al [14] demonstrated that neither of these Mx variants (N631 or S631) had GTPase activity, which is essential for antiviral activity [16].…”
Section: Introductionmentioning
confidence: 99%
“…A non-synonymous mutation at position 2032 of chicken Mx gene responsible for variation of aminoacid (Ser to Asn) in protein has been demonstrated to be responsible for negative to positive antiviral activity of Mx protein (Ko et al, 2002(Ko et al, , 2004. Recently this SNP have been demonstrated to confer more resistance in chicken to in vivo experimental infection of highly pathogenic avian influenza virus (HPAIV) (Ewald et al, 2011, Wang et al, 2012, Fulton et al, 2014. SNP at 2032 have been analyzed in various chicken breeds (Li et al, 2006, Seyama et al, 2006, Balkisson et al, 2007.…”
Section: Introductionmentioning
confidence: 99%